Usefulness of Six Diagnostic and Screening Measures for Undernutrition in Predicting Length of Hospital Stay: A Comparative Analysis - Rita S. Guerra (2015)
Background Undernutrition has been associated with longer length of hospital stay (LOS). However, an analysis that investigates the association of recommended undernutrition diagnostic and screening indicators with LOS conducted in patients with a varied spectrum of pathologies and considering confounders would help to clarify their clinical value. Objective We aimed to quantify the association of being undernourished as evaluated by different methodologies with LOS and their validity in predicting inpatient LOS. Design A prospective observational study was conducted. Undernutrition was evaluated by the Academy of Nutrition and Dietetics-American Society for Parental and Enteral Nutrition recommended clinical characteristics of malnutrition (AA-CCM) tool, the Patient-Generated Subjective Global Assessment (PG-SGA), the Nutritional Risk Screening (NRS-2002) tool, and the Malnutrition Universal Screening tool (MUST). Handgrip strength (HGS) quartiles by sex and phase angle (PA) categories were also used as indicators of undernutrition. Participants and setting Six hundred eighty-two inpatients from a Portuguese university hospital participated between 2011 and 2013. Main outcome measures LOS was determined between the date of hospital admission and discharge. Statistical analyses performed Kaplan-Meier and adjusted Cox proportional hazard ratio (HR) methods were applied. Results Moderate or severe undernutrition by AA-CCM (HR 0.58, 95% CI 0.49 to 0.69), by PG-SGA (moderate or suspected: HR 0.60, 95% CI 0.49 to 0.73 and severe: HR 0.52, 95% CI 0.42 to 0.64), risk of undernutrition assessed by NRS-2002 (HR 0.61, 95% CI 0.52 to 0.73), by MUST (medium: HR 0.75, 95% CI 0.60 to 0.95 and high: HR 0.67, 95% CI 0.55 to 0.81), HGS quartile (second: HR 0.64, 95% CI 0.50 to 0.80 and first [lowest]: HR 0.50, 95% CI 0.39 to 0.64) and nutritional risk defined by low PA (HR 0.62, 95% CI 0.48 to 0.81) were all independently associated with lower probability of being discharged from the hospital. Conclusions Despite assessing different dimensions of nutritional status, undernutrition by AA-CCM and PG-SGA, risk of undernutrition assessed by NRS-2002 and MUST, and low HGS and PA independently predict longer LOS in hospitalized patients. All these methodologies share a similar validity in predicting LOS.